The Right of People with Disabilities to Access Information: Preventive Information from COVID-19 as an Example - Boumaned, Hadjer (Journal of Legal Studies and Researches, 2021)
Persons with disabilities enjoy the right to access information, as it is a human right in accordance with international legislation, including national legislation in Algeria. In order to ensure that people with disabilities have access to various preventive information related to Covid 19 virus, a number of measures have been taken at the international and national levels